If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3f + -11 = 4 Reorder the terms: -11 + 3f = 4 Solving -11 + 3f = 4 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 3f = 4 + 11 Combine like terms: -11 + 11 = 0 0 + 3f = 4 + 11 3f = 4 + 11 Combine like terms: 4 + 11 = 15 3f = 15 Divide each side by '3'. f = 5 Simplifying f = 5
| -8+9c=19 | | 1/4x=24-1/2x | | 8+9c=19 | | 4/5X1/3= | | -12x-12x^2=0 | | (Z+2)(9x-5)=0 | | 12x+y=-3 | | 2b^2+5b-63=0 | | 261=79-x | | 1/x-1/x+1=1/x(2)+x | | 27-6z=-5(7z-9) | | X*2X=166 | | -16=4y-9 | | 2(8b+2)-1+4g-(2-5g)= | | -x-7=x+1 | | x=160-(170-x) | | 43=3u-11 | | x^3-12x^2-6x-12=0 | | 33b-23=b | | 29-5x=9-7x | | 12A-7=-1 | | y=0.15x+0.15 | | 7-4a=2a+2-5a | | 12=6-2y | | y-1=1/5(x-3) | | solvingx^3-12x^2-6x-12=0 | | -7-x=1+x | | -(7-7a)+4a=-23+3a | | 20x^2(-3+4x)=0 | | 1/3x-5/6x=17 | | 157=11-w | | 21x+42=-3 |